A note on p-adic q-ζ-functions II - Dąbrowski, Andrzej (Journal of mathematical analysis and applications, 2014)
We show that p-adic q-ζ-function constructed by Koblitz [7] (see also Dąbrowski [4]) can be obtained as Γ-transform of some p-adic measure coming from Lubin–Tate formal group.